(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Interest to structural application of textile reinforced polymer matrix composite materials (CM) is growing during last years. In different branches of machine building, aerospace, automotive and others industries we can find structural elements preferably be produced using such reinforcement. At the same time, such materials are exhibiting elastic and strength properties scatter. In the framework of the present investigation, we observe yarn penetrated by a resin in a composite as a reinforcing “macro” fiber. Such “macro” fiber mechanical properties were measured experimentally, for this purpose was produced and was tested by tension until fracture fiber samples, having different length. Then was elaborated and was realized structural strength probabilistic model. In the textile geometry, was picked out repeating structural element – polymer matrix volume with two curved “macro” fiber’s chunks inside it. Complete composite material volume is possible to represent as a set of repeating structural elements. External loads application leads to disperse structural elements failure. Neighboring to ruptured elements are overloaded leading to higher probability to fail for them. Using FEM was modeled stress state in “macro” fibers inside CM. Then, was numerically obtained stress distribution in composite material, having different number of broken loops. Probabilities of different numbers of failed elements were calculated. Strength probability function, based on Weibull approach was obtained. CM samples were tested under tension and obtained results were compared with numerical modeling as well as were analyzed.